Characterization by restriction endonuclease analysis and DNA hybridization using IS900 of bovine, ovine, caprine and human dependent strains of Mycobacterium paratuberculosis isolated in various localities - Pavlík, I; Bejcková, L; Pavlas, M; Rozsypalová, Z; Kosková, S (Veterinary microbiology, 1995)
DNA of 90 mycobactin-dependent strains of Mycobacterium paratuberculosis, isolated in 9 countries, was digested with restriction endonuclease PstI and hybridized with a DNA fragment containing insertion sequence IS900. Bovine strains (n = 73) were isolated from 61 animals in 17 herds, ovine strains (n = 15) from 13 animals in 3 herds and the set was completed by 1 caprine and 1 human (Linda) strain. Three types, tentatively designated A (n = 37), B (n = 51) and C (n = 2) were differentiated by restriction fragment length polymorphism (RFLP). Of the bovine strains 27, 45 and 1 were classified as belonging to types A, B and C, respectively; of the 15 ovine strains 10 and 5 belonged to types A and B, respectively; the caprine strain belonged to type C. The human strain Linda, isolated in the U.S.A., from a man with Crohn's disease, belonged to B type. A certain degree of type uniformity was observed among strains isolated within one herd in the course of several years, and the prevalence of a single type was also recorded within individual regions of the Czech Republic and Slovakia. Type A was identified in the course of 2 years in a sheep farm with frequent sales and purchases of animals, and type C was demonstrated in a goat kept in the same farm. Differences between RFLP types of the strains isolated from mesenteric lymph nodes and intestinal mucosa were found in one cow and one sheep. Selected strains of M. paratuberculosis RFLP type A (14 strains) and B (18 strains) were digested with restriction endonuclease BstEII. All the strains of A type were classified into C1 group and all the strains of B type into Cx group.
Keywords: Sheep; Deoxyribonucleases, Type II Site-Specific; DNA bakterií; Humans; druhová specificita; Polymorphism, Restriction Fragment Length; restrikční mapování; DNA fingerprinting; kozy; DNA Fingerprinting; Mycobacterium avium subsp. paratuberculosis; lidé; zvířata; DNA, Bacterial; Cattle; restrikční endonukleasy typu II; Goats; Restriction Mapping; skot; DNA Transposable Elements; Species Specificity; Nucleic Acid Hybridization; hybridizace nukleových kyselin; Animals; polymorfismus délky restrikčních fragmentů; transpozibilní elementy DNA; ovce